One world, no hunger initiative. Enhancing technical support to potato working groups in Cameroon, India, Kenya, Mali, Nigeria, Tunisia and Uganda. Project profile. - International Potato Center (International Potato Center, 2020)
Members of the potato working groups will benefit from access to international expertise and the mutual exchange of information and innovations to boost potato production in their respective countries.